The killing compartments : the mentality of mass murder - Swaan, Abram de 1942- (Yale University Press, 2015)
The twentieth century was among the bloodiest in the history of humanity. Untold millions were slaughtered. How people are enrolled in the service of evil is a question that continues to bedevil. In this trenchant book, Abram de Swaan offers a taxonomy of mass violence that focuses on the rank-and-file perpetrators, examining how murderous regimes recruit them and create what De Swaan calls the "killing compartments" that make possible the worst abominations without apparent moral misgiving, without a sense of personal responsibility, and, above all, without pity.--Provided by publisher